Rapid Evidence Assessment: Mentoring Interventions for/by Students with Disabilities at Third-Level Education - Adriana Cardinot; Paul Flynn (MDPI AG, 2022)
The number of students with disabilities enrolling in higher education has shown an increase across the world. Despite this, many students with disabilities still encounter several barriers in transitioning to third-level education. Educational mentoring programmes have emerged as interventions that have the potential to provide peer support and reduce isolation in higher education. However, there is little understanding of how this intervention could benefit students with disabilities in mentor and mentee roles. This systematic review aimed to collate, synthesise, and compare empirical studies describing mentoring programmes, interventions, or initiatives in which undergraduates with disabilities acted as mentors or mentees. The study employs a rapid evidence assessment methodology to gather, analyse, and compare relevant publications describing mentoring interventions involving students with disabilities. The search was limited to studies published between 2010 and 2021. In total, eleven studies met the PICO criteria established in this review. The results obtained in this study present evidence of the multiple benefits and key elements of mentoring programmes for/by students with disabilities to facilitate the transition to higher education in social and academic engagement. In particular, it was found that mentoring programmes can have an impact on mentors and mentees, such as the feeling of empowerment, a sense of belonging in the university, normalising academic challenges, and increased empathy and awareness of disabilities. Key recommendations for designing mentoring interventions involving students with disabilities are also outlined.